Menyebarkan Kebaikan lewat Konsep “Pay it Foward” dalam Kegiatan Pembelajaran - Harrys Cristian Vieri; Mujahid Widian Saragih (Yayasan Literasi Sains Indonesia, 2023)
Education is an important part in the history of human civilization. In history, education has changed many things, such as lifestyle, developments in the social structure of society, and many more. Therefore, it is important to pay more attention to efforts to develop education. But in Indonesia itself, it seems that education is still not getting better attention, because political instability, chaotic economic conditions, and underdeveloped socio-cultural conditions make education an issue that has a low priority. In the reform era, various regimes have tried to raise the issue of education as one of the priority issues. In the era of President Jokowi, there were various policies related to education issues. One of them is the teaching campus. The teaching campus itself is a program where students can practice their knowledge in a designated school. The teaching campus itself has been implemented in various public and private campuses in Indonesia. North Sumatra University is one of the universities that organizes teaching campuses. However, the University of North Sumatra has introduced its own version of the teaching campus concept, which is referred to as USU's partner teaching campus. The aim of this program is to improve the quality of education in the province of North Sumatra. The USU Partner Teaching Campus can also be paired with Field Lecture Practices (PKL).